Youth Unemployment in Uruguay. (IMF Working Papers; Working Paper, 2020)
Uruguay enjoys favorable social outcomes, and its labor indicators are comparable to other Latin American countries, but its youth unemployment is one of the highest in the world. To help understand this duality, we employ synthetic panels from repeated household surveys for LA6 countries from 1990-2018 to investigate the determinants of the youth-to-adult unemployment gap. We find that a large part of the Uruguayan gap cannot be explained by standard variables, which opens the possibility that other uncontrolled factors, including labor market institutions, might be at play.